In situ investigation of particle clustering dynamics in colloidal assemblies using fluorescence microscopy - Suh, Youngjoon; Gowda, Hamsa; Won, Yoonjin (Journal of colloid and interface science, 2020)
Herein, particle clustering dynamics and thermofluidic transprot in colloidal assemblies are experimentally examined using a novel fluorescence technique with the aim to investigate colloidal physics that decide cracking mechanics during self-assembly. The results show that grain boundaries are determined by dynamic structuring regimes governed by the film’s saturation level. [Display omitted] Colloidal self-assembly is a process in which dispersed matter spontaneously form higher-order structures without external intervention. During self-assembly, packed particles are subject to solvent-evaporation induced dynamic structuring phases, which leads to microscale defects called the grain boundaries. While it is imperative to precisely control detailed grain boundaries to fabricate well-defined self-assembled crystals, the understanding of the colloidal physics that govern grain boundaries remains a challenge due to limited resolutions of current visualization approaches. In this work, we experimentally report in situ particle clustering dynamics during evaporative colloidal assembly by studying a novel microscale laser induced fluorescence technique. The fluorescence microscopy measures the saturation levels with high fidelity to identify distinct colloidal structuring regimes during self-assembly as well as cracking mechanics. The techniques discussed in this work not only enables unprecedented levels of colloidal self-assembly analysis but also have potential to be used for various sensing applications with microscopic resolutions.